Single Image Joint Motion Deblurring and Super-Resolution Using the Multi-Scale Channel Attention Modules - Shoyan, Misak T. (Mathematical Problems of Computer Science, 2021)
During the last decade, deep convolutional neural networks have significantly advanced the single image super-resolution techniques reconstructing realistic textural and spatial details. In classical image super-resolution problems, it is assumed that the low-resolution image has a certain downsampling degradation. However, complicated image degradations are inevitable in real-world scenarios, and motion blur is a common type of image degradation due to camera or scene motion during the image capturing process. This work proposes a fully convolutional neural network to reconstruct high-resolution sharp images from the given motion blurry low-resolution images. The deblurring subnetwork is based on multi-stage progressive architecture, while the super-resolution subnetwork is designed using the multi-scale channel attention modules. A simple and effective training strategy is employed where a pre-trained frozen deblurring module is used to train the super-resolution module. The deblurring module is unfrozen in the last training phase. Experiments show that, unlike the other methods, the proposed method reconstructs relatively small structures and textural details while successfully removing the complex motion blur. The implementation code and the pre-trained model are publicly available at https://github.com/misakshoyan/joint-motion-deblur-and-sr.